Synthesis Wanted: Reading Capital After 20th Century Orthodoxies and Revisions - Ingo Schmidt (tripleC: Communication, Capitalism & Critique, 2018)
The article distinguishes between revisionist and orthodox readings of Capital and identifies two waves of innovations in Marxist political economy. The first produced the classical theories of imperialism; the second produced a diversity of Neo-Marxisms and new orthodoxies sowing the seeds for the 1000 Marxisms developing in the age of neoliberal globalisation. Reading all of these approaches to Marxist Political Economy in context, the article suggests and offers a key to the understanding of capitalist development and socialist movements in the 20th century. Using them as background for a new reading of Capital also allows an understanding of contemporary capitalism and considerations of socialist futures.